2022
DOI: 10.3390/ijerph19095715
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acceptability and Initial Effectiveness of a Unified Protocol Prevention Program to Train Emotional Regulation Skills in Female Nursing Professionals during the COVID-19 Pandemic

Abstract: Healthcare professionals, especially women, have shown increases in anxious-depressive symptoms as a consequence of the COVID-19 pandemic. The aim of this pilot study was to evaluate the acceptability and preliminary effectiveness of a Unified Protocol (UP) prevention program to provide emotional regulation skills to cope with stressful situations. The sample consisted of 27 nursing professionals (100% women; mean age: 45.67; SD = 7.71) working in a Spanish public hospital during COVID-19, who were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Fourteen studies focused on different burnout interventions (Akugue, 2022; Azizoddin et al, 2021; Blake et al, 2020; Crippa et al, 2021; Cunningham et al, 2017; Dincer & Inangil, 2021; Ferreres‐Galán et al, 2022; Giordano et al, 2022; Horn et al, 2019; Hsieh et al, 2022; Miyoshi et al, 2022; Sawyer et al, 2022; Sijbrandij et al, 2020; Sis Çelik & Kılınç, 2022). Of these studies, 13 assessed the effectiveness of an intervention, and one reported the development and usability of an intervention (Blake et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies focused on different burnout interventions (Akugue, 2022; Azizoddin et al, 2021; Blake et al, 2020; Crippa et al, 2021; Cunningham et al, 2017; Dincer & Inangil, 2021; Ferreres‐Galán et al, 2022; Giordano et al, 2022; Horn et al, 2019; Hsieh et al, 2022; Miyoshi et al, 2022; Sawyer et al, 2022; Sijbrandij et al, 2020; Sis Çelik & Kılınç, 2022). Of these studies, 13 assessed the effectiveness of an intervention, and one reported the development and usability of an intervention (Blake et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…One of them used ordinary mail to send the materials (Procaccia et al., 2021). The other two administrated their interventions in person (Ferreres et al., 2022; Yildirim & Yildiz, 2022). The length of interventions ranged between 1 day and 8 weeks, only 3 studies reported follow‐up data (Amsalem et al., 2022; Ferreres et al., 2022; Fiol‐DeRoque et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Ferreres et al. (2022) proved the effectiveness of a preventive programme to train emotional skills in healthcare professionals. In the pre‐ and post‐test intragroup comparisons, only the intervention group presented significant differences for depression (MD = −2.16, p = 0.024, Cohen's d = −0.40), stress (MD = −2.08, p = 0.039, Cohen's d = −0.48) and personal accomplishment (MD = −5.77, p = 0.036, Cohen's d = −0.76).…”
Section: Resultsmentioning
confidence: 99%
“…Other techniques that have already been used with healthcare workers with favorable results were Yoga ( 48 ) and Tai Chi ( 49 ) sessions seeking to reduce anxiety symptoms and improving sleep quality. Protocols for teaching emotional regulation techniques to healthcare personnel have also been tried and have shown efficacy in their initial applications, so further research on these aspects is needed ( 50 ).…”
Section: Discussionmentioning
confidence: 99%